Relation between self-perceived stress, psychopathological symptoms and the stress hormone prolactin in emerging psychosis. (April 2021) - Studerus, Erich; Ittig, Sarah; Beck, Katharina; Del Cacho, Nuria; Vila-Badia, Regina; Butjosa, Anna; Usall, Judith; Riecher-Rössler, Anita
Abstract: Background: Psychosocial stress and the stress hormone prolactin are assumed to play an important role in the pathogenesis of schizophrenia and related psychoses, and have been frequently observed to be increased in antipsychotic-naïve patients with a clinical high risk for psychosis (CHR-P) or first episode of psychosis (FEP). The aim of this study was to further elucidate the relationships between self-perceived stress, psychopathological symptoms and prolactin levels in these patients. Methods: In this cross-sectional study, 45 healthy controls, 31 CHR-P patients and 87 FEP patients were recruited from two different study centers. Prolactin was measured under standardized conditions between 8 and 10 am. All patients were antipsychotic-naïve and not taking any prolactin influencing medication. Self-perceived stress during the last month was measured with the perceived stress scale (PSS-10) immediately before blood taking. Results: Both CHR-P and FEP patients showed significantly higher levels of self-perceived stress and prolactin than controls. Hyperprolactinemia (i.e. prolactin levels above the reference range) was observed in 26% of CHR-P and 45% of FEP patients. Self-perceived stress was significantly positively associated with affective symptoms, but not with other symptoms. There was no significant association between self-perceived stress and prolactin levels. Conclusion: Our results confirm that CHR-P and FEP patients have higher stress levels than healthy controls and frequently have hyperprolactinemia, independent of antipsychotic medication. However, although it is well established that prolactin increases in response to stress, our results do not support the notion that increased prolactin levels in these patients are due to stress.